Best Approaches in Teaching Lexis to Young Learners (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This paper examines the most effective methods for teaching vocabulary (lexis) to young language learners. A review of relevant literature explores theoretical foundations and empirical research on lexis acquisition and instructional approaches tailored to children. Key factors impacting the learning of new words are analyzed, including age, cognitive development, memory processes, motivation and engagement. Core methodologies are presented such as extensive reading, multimedia resources, games and activities, along with guidelines for creating a rich language environment. Challenges specific to teaching young learners are discussed, with practical recommendations offered to educators. The paper concludes that a diverse repertoire of meaningful, contextualized and interactive techniques implemented through a structured, consistent program best enables robust youth vocabulary growth.